(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The coronavirus disease 2019 (COVID-19) become pandemic in many countries. Many subsequent data shown that the obesity is a risk factor responsible for severity of COVID-19. Obese COVID-19 patient were significantly associated with elevation the inflammatory markers and coagulated factor. The sex has association with diseases severity specially obese COVID-19 patient, so more likely to become seriously ill ,so those patients will hospitalized and admitted to ICU and more care requirement .Objective: The ambition of this study is to investigation whether obesity is implicated in exacerbation severity of COVID .19.Method: 381 COVID -19 patient was participated in this study,185 of them were non obese COVID-19 and the other 196 patient were Obese COVID-19, inflammatory and coagulation marker was measured.Results: The data show significant higher levels in interleukins IL-6, CRP, TNF-α, Ferritin, and D-dimer and failure to give significant level for IL-10 and glucose concentration among obese , and non-obese, obese based on BMI and depend on the sex .Conclusion: Obesity is significantly increase the severity of COVID-19 disease. The obese patient displays higher levels for inflammatory and coagulation factor specially in those patients has 35-39.9 BMI compared with normal weight individuals. The data indicated that the sex significantly interact with obesity on to COVID-19 severity enhancing.